The Influence of the Effectiveness of Pondok Rules Communication Delivered by Administrators through Room Leader on Students' Understanding - Bashori, Abdul Hamid; Gautama, Sidartha Adi; Abnisa, Almaydza Pratama; Hayatina, Lamya Hayatina; Hubur, AA (STAI Publisistik Thawalib Jakarta, 2024)
Student’s understanding of pondok regulations is influenced by both direct and indirect communication processes, making it necessary to investigate in order to improve discipline and compliance. This study aims to examine the effect of communication effectiveness regarding pondok regulations, delivered by administrators and room leaders, on student’s understanding both directly and indirectly using path analysis. A quantitative approach was used with path analysis through linear regression assisted by SPSS, and total sampling of the entire population. The results show: communication from administrators to student does not significantly affect student’s understanding (sig. 0.721 > 0.05). Communication from administrators to room leaders has a significant effect (sig. 0.032 < 0.05). Communication from room leaders to student’s does not significantly affect student’s understanding (sig. 0.798 > 0.05). Lastly, the direct influence of administrator communication is greater than the indirect influence through room leaders. Conclusion: communication through room leaders does not affect student’s understanding as no significant communication path is formed.